2019
DOI: 10.1016/j.adolescence.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parentalguanand school adjustment among Chinese early adolescents: The moderating role of interdependent self‐construal

Abstract: Introduction: Previous research suggests that supportive parenting is positively related to adolescents' academic and psychological functioning. However, most extant research has focused on parenting styles observed in Western countries, whereas less is known about the role of culturally specific parenting dimensions in Eastern countries such as China. The purpose of this study was to examine the association between parental guan and school adjustment in Mainland Chinese early adolescents, postulating moderati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 71 publications
(76 reference statements)
4
37
0
1
Order By: Relevance
“…The average score of these items was calculated, with a higher value indicating higher levels of social competence at school. Previous research reported good internal consistency of this scale among Chinese students (Lan et al, 2019c). Cronbach's alpha was 0.74 in the present study.…”
Section: Social Competencementioning
confidence: 72%
See 4 more Smart Citations
“…The average score of these items was calculated, with a higher value indicating higher levels of social competence at school. Previous research reported good internal consistency of this scale among Chinese students (Lan et al, 2019c). Cronbach's alpha was 0.74 in the present study.…”
Section: Social Competencementioning
confidence: 72%
“…According to the existing evidence, Lan et al (2019c) have demonstrated that interdependent self-construal can moderate the association between parental governing/training and school adjustment in Chinese students. To be precise, students with high parental governing/training and an interdependent selfconstrual exhibit high teacher-rated social competence and better academic grades.…”
Section: The Moderating Role Of Social Identitymentioning
confidence: 99%
See 3 more Smart Citations